FENOMENA MENGEMIS DI JEJARING MEDIA SOSIAL DALAM PERSPEKTIF AL-QUR’AN - Siti Zahraini; Randy Dwi Alvianto; Meisya Dewi Putri (IAT IAIN Pontianak, 2023)
The current surge in the practice of begging can be attributed to the ever-expanding influence of technology. Technological advancements, constantly evolving and facilitating communication and interactions, have provided people with unprecedented convenience. However, the misuse of technology, particularly through social media platforms, has led to the emergence of a concerning trend –the phenomenon of online begging. While technology's presence was anticipated to yield positive outcomes, its misapplication has given rise to this issue. Employing a qualitative approach and drawing from various literature sources, this discourse delves into the implications of social media on the upsurge of begging, examining it from both a general perspective and an Islamic standpoint. Islamic scriptures, notably the Qur'an, contain relevant verses that address the matter of online begging. These verses include Q.S Adz-Dzariyat verse 19, Al-Ma'arij verses 24-25, Ad-Dhuha verse 10, and Al-Hujurat verse 11. Islamic scholars express disapproval of begging, advocating that those possessing physical capability should seek alternative means of employment instead.